Tumour-inhibitory and antimetastatic effects of IL-2 in mice carrying MHC class I- tumours of HPV16 origin - Indrová, Marie; Bubeník, Jan; Mikysková, Romana; Vonka, Vladimír; Smahel, Michal; Zák, Roman; Símová, Jana; Bieblová, Jana; Mendoza, Luis; Jandlová, Tána (International journal of oncology, 2002)
Oncogenic, moderately immunogenic, MHC class I- and class II-, B7-, MK16/1/III ABC (MK16) cells were previously established by co-transfection of HPV16 E6/E7 and activated H-ras oncogene DNA into C57BL/6 kidney cells. Subcutaneous transplantation of these cells produced progressively growing local neoplasms which metastasized spontaneously to lungs and lymph nodes. The MK16 cells were implanted into syngeneic mice and used to examine whether the tumour lacking the signal molecules required for the induction of and sensitivity to T cell immunity is susceptible to local IL-2 treatment and IL-2 gene therapy. Peritumoural administration of human rIL-2 or murine IL-2 gene-modified MK16 tumour vaccine inhibited growth of subcutaneous MK16 tumour transplants and reduced the number of their lung metastases. Spleen cells from MK16 tumour-immunized mice were not cytolytic when allowed to react with the MK16 target cells, although they efficiently lysed the MHC class I+ malignant TC1 cells, obtained from C57BL/6 lung cell cultures after transfection with the same plasmids as those used for the derivation of the MK16 cells. However, when the MK16 cells were cultivated in vitro in the presence of IFNgamma, they acquired, together with the expression of MHC class I molecules, the sensitivity to the cytolytic effect of spleen cells from the MK16 tumour-immunized mice. These results indicate that experimental tumours which are MHC class I- and mimick in this respect a high proportion of human HPV16-associated carcinomas are suitable for IL-2 treatment.
Keywords: transplantace nádorů; down regulace; Neoplasm Metastasis; protinádorové látky; Interleukin-2; Neoplasm Transplantation; cytokiny; Flow Cytometry; Time Factors; průtoková cytometrie; Animals; lidé; Down-Regulation; interleukin-2; Papillomaviridae; Humans; zvířata; časové faktory; myši inbrední C57BL; nádorové buňky kultivované; myši; Mice, Inbred C57BL; Cytokines; Tumor Cells, Cultured; Mice; metastázy nádorů; geny MHC třídy I; Genes, MHC Class I; Antineoplastic Agents